Anamnestic broadly reactive antibodies induced by H7N9 virus more efficiently bind to seasonal H3N2 strains. Issue 6 (30th November 2022) - Chen, Yao; Hilchey, Shannon P.; Wang, Jiong; Garigen, Jessica; Zand, Martin S.; Huang, Junqiong
ABSTRACT: The very first influenza virus exposure in a human during infancy is known to imprint the host immune system. However, it is unclear how the memory B cells that first target virus epitopes affect antibody response to the stalk of hemagglutinin (HA) domain of influenza virus. Our study is designed to measure the cross-reactivity of antibodies induced by inactivated H7N9 virus using isolated human peripheral blood B cells. Most of the participants displayed higher levels of plasma IgG against the seasonal strains A/Vic11 and A/Cali09 than those binding to historical outbreak A/HK68 and A/PR8. H3 stalk-binding antibodies were detected in plasma at a 1:5000 dilution in 12 of 13 donors, H1 stalk-binding antibodies in all donors, indicating the existence of H3 and H1 stalk-reactive memory B cells. A moderate to high level of broadly cross-reactive antibodies was induced in memory B cells from all donors after in vitro stimulation of B cells with H7N9 virus. H3 stalk-binding antibodies were also detected in most subjects, with cross-reactivity to H1 and H7 stalk domains. The stalk-reactive antibodies bound to five H3 strains spanning 45 years and different H1, H2, H3, H5, H6, H7, H9 and B strains. Interestingly, H1- and H3-reactive IgG were much higher than H7-binding antibodies after 6 days of H7N9 stimulation. Our results demonstrate that HA stalk-reactive antibodies induced by H7N9 viruses more efficiently bound to yearly circulating both H3N2 and H1N1 strains than the boosting strain, indicating that HA stalk immunological imprint can be extended across currently circulating strains or vaccines.